Dampak Covid-19 terhadap Pendapatan Pedagang di Waterfront Kota Pontianak - Amama, Rhiendang; Yulia, Yulia; Jayanti, Fitri (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
This study aims to find and analyze the income of Pontianak City Waterfront traders before and during the Covid-19 pandemic, and the efforts made by Pontianak City Waterfront traders in overcoming obstacles during the Covid-19 pandemic. This study uses a descriptive method and a qualitative approach. Sources of data come from primary and secondary data. Primary data are the Waterfront traders in Pontianak City and secondary data are obtained from books, journals, and articles related to research. Data collection techniques were carried out by means of observation, direct interviews, and documentation. The results obtained from the research include: before the Covid-19 pandemic, the average income of Waterfront traders was IDR 100,000 to IDR 700,000 per day. The income of Pontianak City Waterfront traders during the Covid-19 pandemic is divided into three parts of time, namely income during PSBB, New Normal, and PPKM. During the PSBB, the income of traders was Rp. 0. During the New Normal and PPKM, it fell to an average of Rp. 80,000-Rp. 400,000. During the New Normal and PPKM, there was a decrease in the income of traders with an average decrease of 20-75% per day. The decline in income has an impact on the daily life of traders. There are various efforts by traders to overcome obstacles during the Covid-19 pandemic, this is done by traders so that they can still sell during the Covid-19 pandemic.